The Impact of Blockchain Security on Cryptocurrency Investment Preferences Among Millennials in Indonesia - Felisia Christiani; Cicilia Sriliasta Bangun; Riya Widayanti (Blockchain Frontier Technology, 2024)
This study explores the impact of blockchain security on cryptocurrency investment preferences among millennials in Indonesia. Despite the high volatility of cryptocurrencies, they continue to attract a significant number of millennial investors, driven by perceptions of security and potential high returns. The study aim of this research is to investigate how blockchain security influences the investment preferences of millennial investors, particularly concerning their decision-making process in the cryptocurrency market. This study employs a quantitative approach, gathering data through surveys targeting millennial cryptocurrency investors. The data is analyzed using Structural Equation Modeling (SEM) to assess the relationships between blockchain security perceptions and investment preferences.This research provides new insights by integrating blockchain security as a key factor influencing investment decisions, bridging the gap between technical and psychological aspects of investment behavior. While there is substantial research on cryptocurrency investments, limited stud-ies address the specific influence of blockchain security on investment preferences, particularly in the context of millennial investors in Indonesia. The finding suggest that blockchain security significantly shapes the investment preferences of millennials, fostering trust and influencing their decision to engage in cryptocurrency investments. This study offers valuable insights for blockchain developers and regulators to enhance security features, helping to build investor confidence in Indonesia rapidly expanding cryptocurrency market.